(untitled) (UNIZIK Journal of Marketing, 2024)
This research examined the effect of digital marketing channels on customer patronage of online shops. The objectives of the study were to determine the significant effect of e-mail marketing, social media marketing, affiliate marketing and search engine marketing on customer patronage of Jumia and Konga online shops. The study adopted a cross-sectional design. Primary data were collected using structured online questionnaire. It was impossible to obtain the total population of the study; therefore, the researcher employed the use of Conchran formula for sample size determination for an unknown population size. Purposive sampling technique was used to select 384 online customers of Jumia and Konga in Abia State, Nigeria. Data collected were analyzed using descriptive and inferential statistical tools. Consequent upon analysis, it was revealed that social media marketing, and search engine marketing had a significant positive effect on customer patronage of online shops. It was also found that e-mail marketing and affiliate marketing do not have a significant effect on customer patronage of online shops. Based on the findings, the study concluded that content, social media and search engine marketing significantly enhance customer patronage while e-mail and affiliate marketing do not have a significantly influence on customer patronage of online shops. It was recommended among other things that online shops especially Jumia and Konga under study should frequently review their use of various digital marketing channels in advertising and promotion of their products to constantly be in line with current and emerging trends.